Lectin-like oxidized low density lipoprotein receptor 1-deficient mice show resistance to instability-induced osteoarthritis. (2nd September 2016) - Hashimoto, K; Mori, S; Oda, Y; Nakano, A; Sawamura, T; Akagi, M
Abstract : Objectives : The lectin-like oxidized low density lipoprotein (ox-LDL) receptor 1 (LOX-1)/ox-LDL system, which contributes to the pathogenesis of atherosclerosis, may be involved in the development of osteoarthritis (OA). However, the mechanisms by which the LOX-1/ox-LDL system contributes to OA development in vivo are unclear. In this study, we investigated the direct involvement of LOX-1/ox-LDL in OA development by using LOX-1-knockout (LOX-1 – / – ) mice in a joint instability-induced model of OA. Method : OA development was evaluated with histological scoring at 4 and 8 weeks after surgery to induce knee destabilization in LOX-1 + / + and LOX-1 – / – mice. Immunohistological analysis was used to evaluate the expression of LOX-1, ox-LDL, Runt-related transcription factor 2 (Runx2), and type X collagen (COL X) in articular chondrocytes and osteophyte-forming cells. In addition, double immunofluorescence staining was performed to determine the relationships between LOX-1 and Runx2 or COL X expression. Results : In the model of knee destabilization, symptoms were significantly suppressed in LOX-1 – / – mice. LOX-1, ox-LDL, Runx2, and COL X were overexpressed in articular chondrocytes and osteophyte-forming cells in LOX-1 + / + mice and were significantly downregulated in articular chondrocytes and osteophyte-forming cells in LOX-1 – / – mice compared with those in LOX-1 + / + mice. Double immunostaining indicated that LOX-1 localization coincided with Runx2 and COL X expression. Conclusions : These data indicate that the LOX-1/ox-LDL system plays a pivotal role in the pathogenesis of instability-induced OA through endochondral ossification. LOX-1-positive chondrocytes and osteophyte-forming cells may be possible targets to prevent disease progression in OA.